Nursing of an elderly patient with COVID-19 treated with extracorporeal membrane oxygenation (1例高龄新型冠状病毒感染患者行体外膜肺氧合治疗的护理) - ZHAO Xiaowei (赵潇薇); YANG Caifu (杨财富) (中西医结合护理)
This article summarized the nursing management of an elderly patient with COVID-19 treated with extracorporeal membrane oxygenation(ECMO). Based on the monitoring on vital signs of the patient, comprehensive nursing interventions were carried out to prevent the bleeding, thrombosis, hemolysis, infection and other complications, as well as catheter-associated infection, during ECMO treatment. In addition, catheter maintenance, prone position ventilation, management of unplanned extubation, and prevention of pressure injuries and i were enhanced to ensure the safety of patient during ECMO treatment. (总结1例高龄新型冠状病毒感染患者行体外膜肺氧合(ECMO)治疗的护理经验。在完善生命体征监测的基础上, 积极预防ECMO治疗期间出血、栓塞、溶血等并发症和感染, 加强管道护理、俯卧位通气和非计划拔管的护理, 预防压力性损伤。)